Etiological indicators of the Simmental breed of cattle (Texas Journal of Agriculture and Biological Sciences, 2022)
The article presents data on the ethological indicators of Simmental cattle at the age of 6 and 18 months (standing, chewing, eating, sleeping, general activity index).